PENGGUNAAN LINGKUNGAN SEBAGAI SUMBER BELAJAR UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN SENI RUPA DI KELAS X MIA 3 SMAN 15 PADANG - 17. Elvandril Adhari, Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of the researchers in the study was to improve creativity and learning outcomes by using the environment as a source of learning in learning art in class X MIA 3 of SMA Negeri 15 Kota Padang. The research method used is classroom action research. The research instrument is the test of student learning outcomes, student creativity questionnaire, observation sheet of student learning activities, teacher teaching activity sheet. The results of the study state that 1). The use of the environment as a learning resource can increase students' creativity in learning Fine Arts in class X MIA 3 of Padang State High School 15, 2). The use of the environment as a learning resource can improve student learning outcomes in learning Fine Arts in class X MIA 3 Padang 15 High School.Keywords: Environmental studies, learning outcomes, significant